Online grocery shopping adoption: do personality traits matter?. Issue 3 (12th February 2020) - Piroth, Philipp; Ritter, Marc Sebastian; Rueger-Muck, Edith
Abstract : Purpose: This study examines the relationship between personality traits and the willingness to buy groceries online. Our research is based on research on consumer values regarding online grocery shopping (OGS), and the authors argue that customer values are aggregated states of personality traits. The authors, therefore, propose the predictive power of personality traits toward OGS usage adoption. Design/methodology/approach: For a more thorough evaluation of the matter, the authors conducted an online administered questionnaire resulting in N  = 678 valid responses and conducted structural equation modeling using IBM AMOS (Vers. 25). Findings: The authors found that none of the five personality traits had a significant influence on the attitude toward OGS. However, subjective norm had strong influence on attitude, and both subjective norm and attitude were solid predictors of purchase intention for groceries online. Unsurprisingly, the attitude toward OGS was higher for consumer groups with prior experience. The results indicate a high relevance of peer groups in the decision-making process of buying groceries online and the crucial importance of the initial purchase. Practical implications: Practitioners, therefore, may resort to marketing the strategies to peer groups and initial purchasing behavior and address the level of experience with the usage of OGS, as well as situational aspects. This may be facilitated by precisely targeted online marketing activities and marketing service strategy adaptations. Originality/value: This is the first study to examine the influence of personality traits toward the willingness to conduct OGS with an emphasis on the lower overall adoption within Germany. The authors furthermore validate the predictive power of the theory of planned behavior (TPB) construct for the economically attractive market segment of OGS by adapting and enhancing the scope of previous research.